Virtue Ethics as Philosophical Foundation for Environmental Education - Tete, Francis; Ariche, Chrisantus Kanayochukwu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This paper is concerned with the philosophy of environmental education. It is premised on the urgent need for environmental education as acknowledged by the United Nations through the United National Educational, Scientific and Cultural Organization in 1972 and through UNEP’s Environmental Assessment of Ogoniland (2011) among other documentations. Drawing on the fundamental role played by philosophy in education, this paper considers what philosophy of education can help education alter the narrative of the environmental crisis and inspire a new civilization of environmental protection. The paper prospects for a workable environmental philosophy of education from the background of environmental virtue ethics, that is, the ethics of human flourishing as applied to the environment. It argues that virtue ethics offers a unique promise as a philosophy of environmental education despite the naturally multidisciplinary character of environmentalism and the diversity of perspectives in environmental philosophy. It recommends that curriculum planners and educational administrators ensure that the child is made to understand very early on that every harm done to nature is ultimately done to oneself, and that environmental protection is a basic virtue for personal and community wellbeing. It thus prescribes that this perspective should guide education even at the pre-school level, and should continue into postgraduate research. It concludes that the virtue ethics tradition points straight at why an environmental change of behavior is urgent, namely, man’s enlightened self-interest, his flourishing, his wellbeing within the ecological universe in which he is inexorably located.